Impaired T cell proliferation by ex vivo BET-inhibition impedes adoptive immunotherapy in a murine melanoma model. Issue 1 (1st February 2020) - Chee, Jonathan; Wilson, Chelsea; Buzzai, Anthony; Wylie, Ben; Forbes, Catherine A; Booth, Mitchell; Principe, Nicola; Foley, Bree; Cruickshank, Mark N; Waithman, Jason
ABSTRACT: Activation of naïve CD8 + T cells stimulates proliferation and differentiation into cytotoxic T-lymphocytes (CTLs). Adoptive T Cell Therapy (ACT) involves multiple rounds of ex vivo activation to generate enough CTLs for reinfusion into patients, but this drives differentiation into terminal effector T cells. Less differentiated CTL populations, such as stem cell memory T cells, are more ideal candidates for ACT because of increased self-renewal and persistent properties. Ex vivo targeting of T cell differentiation with epigenetic modifiers is a potential strategy to improve cytotoxic T-lymphocyte (CTL) generation for ACT. We established a pipeline to assess the effects of epigenetic modifiers on CD8 + T cell proliferation, differentiation, and efficacy in a preclinical melanoma model. Single treatment with epigenetic modifiers inhibited T cell proliferation in vitro, producing CD44 hi CD62L hi effector-like T cells rather than a stem cell memory T cell phenotype. Most epigenetic modifying agents had no significant effect on ACT efficacy with the notable exception of the bromodomain and extraterminal (BET)-inhibitor JQ1 which was associated with a decrease in efficacy compared to unmodified T cells. These findings reveal the complexity of epigenetic targeting of T cell differentiation, highlighting the need to precisely define the epigenetic targeting strategies to improve CTL generation for ACT.